PENGARUH RASIO AKTIVITAS, RASIO PROFITABILITAS DAN RASIO PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DIBURSA EFEK INDONESIA (BEI) - Andhika andhika Oktari; Irwansyah Irwansyah irwansyah; Salmah Salmah Pattisahusiwa (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
ABSTRACT            ANDHIKA OKTARI, 2018. Effects of Activity Ratios, Profitability ratios, and Market ratios on stock returns in Manufacturing Companies on the Indonesia Stock Exchange (BEI) for 2013-2016 under the guidance of Dr. H. Irwansyah, SE., MM as the first lecturer and Salmah Pattisahusiwa, SE., M.Sc., AK as the second lecturer ...This study aims to reveal how the influence of Activity ratio (TATO), profitability ratios (ROA and ROE) and market ratios (PER and PBV) on stock returns are reflected in the dividend payout ratio (DPR) in manufacturing companies listed on the Indonesia Stock Exchange in the 2013- period 2017. The results of this study indicate that Total Asset Turnover (TATO) has a negative and not significant effect on stock returns which is reflected in the value of the dividend payout ratio (DPR), Return on Assets (ROA), not significant positive effect on stock returns reflected in dividend value payout ratio (DPR), Return on Equity (ROE) has a negative and significant effect on stock returns which is reflected in the value of dividend payout ratio (DPR), Price on Equity (PER) negative effect does not significantly influence stock returns reflected in the dividend payout value ratio (DPR) and Price to Book Value (PBV) have a positive and significant effect on stock returns reflected in the dividend payout ratio (DPR)